(untitled) (Eurasian Journal of Learning and Academic Teaching, 2024)
Proper nutrition is the most important factor in the health of a young athlete, affecting not only his feeling, but also the indicators of physical activity. In order to compensate for energy consumption, activate anabolic processes, restore performance, meet the needs of development and growth, as well as recover after physical and nervous - mental stress, young athletes need an optimal diet with a sufficient amount of proteins, fats, carbohydrates, minerals and vitamins. During periods of intense training and competitive stages, certain requirements are imposed on the order of nutrition and drinking water. Recommendations for the composition of nutrition for young athletes have been developed and are reflected in a number of guidelines, but research shows that the actual nutrition of athletes of the Tashkent City Department of the Archery Federation of Uzbekistan does not meet certain requirements of the recommended norms. The article examines modern approaches to organizing the nutrition of young athletes and gives recommendations for individual correction and support of nutrition, depending on the sports specialty, the nature of physical activity, the stage and individual characteristics of the training process.